Analisis Jinas Tam dalam Surah Al Furqan - Isnaini Anggina Lubis; Kiki Haura Sandi; Sari Annisa Siregar; Harun Alrasyid (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
Jinas is an element of muhassinaat al-lafdziyah, which studies the beauty of language in texts. By definition, jinas consists of two sentences that share similarities in every aspect of their writing, including pronunciation, number of letters, structure (tarkib), and diacritics (harakat). Jinas is divided into two main categories: jinas lafdzi and jinas ma’nawi. The category of jinas lafdzi is further subdivided into jinas tam and jinas ghairu tam. This research aims to analyze jinas tam in Surah Al-Furqan. The method employed is qualitative research with a descriptive approach, utilizing content analysis. Data collection was conducted through library research, which involved searching for and reviewing relevant literature. The analysis results indicate that there are seven examples of jinas tam of the type jinas mumatsal found in Surah Al-Furqan, specifically in the following verses: 3, 11, 14, 47, 61, 62, and 72.